Suatu Upaya Pendampingan Pastoral Kepada Nona “Y” yang Mengalami Trauma Akibat Digigit Seekor Anjing di Pulau Sibandang - Anton Sitorus; Rencan Carisma Marbun (Jurnal Pendidikan Agama dan Teologi, 2025)
Every human being has a different past. Of course, past experiences are various. There are beautiful past experiences and vice versa, depending on what happened. Usually the past that seems very painful, is very difficult to forget, until it leaves a mark in the mind and is difficult to forget. The impact is very large, it can lead to prolonged trauma. To treat it certainly takes a long time and requires pastoral counseling. Counselors must have the expertise to help the client heal the trauma wound. There are various effects of trauma, but in this case, the author specifically examines the trauma caused by being bitten by a dog. For that reason, in this section, the author wants to examine "Assistance Efforts for Miss "Y" who experienced Trauma Due to Being Bitten by a Dog on Sibandang Island".